Who sees the trades? The effect of information on liquidity in inter-dealer markets - Rod Garratt; Michael Junho Lee; Antoine Martin; Robert M. Townsend (Federal Reserve Bank of New York, 2019)
Dealers, who strategically supply liquidity to traders, are subject to both liquidity and adverse selection costs. While liquidity costs can be mitigated through inter-dealer trading, individual dealers' private motives to acquire information compromise inter-dealer market liquidity. Post-trade information disclosure can improve market liquidity by counteracting dealers' incentives to become better informed through their market-making activities. Asymmetric disclosure, however, exacerbates the adverse selection problem in inter-dealer markets, in turn decreasing equilibrium liquidity provision. A non-monotonic relationship may arise between the partial release of post-trade information and market liquidity. This points to a practical concern: a strategic post-trade platform has incentives to maximize adverse selection and may choose to release information in a way that minimizes equilibrium liquidity provision.
Keywords: D62; D82; G14; G23; 330; inter-dealer markets; liquidity; information design; platforms